2021
DOI: 10.3390/biology10090890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Performance Status on the Effectiveness of Pembrolizumab Monotherapy in First-Line for Advanced Non-Small-Cell Lung Cancer: Results in a Real-World Population

Abstract: The KEYNOTE-024 clinical trial showed promising results for pembrolizumab in the first-line of treatment of advanced non-small-cell lung cancer (NSCLC). However, the profile of patients in real-world practice differs from those included in this clinical trial. Here, an observational single-center retrospective study was performed through a comparative analysis of clinical outcomes after pembrolizumab therapy according to the Eastern Cooperative Oncology Group Stage Performance Status (ECOG PS). Moreover, univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Moreover, Santini et al described that a higher proportion of NSCLC patients who had received ICIs within 30 days of death had a PS ≥ 2 [30]. Jiménez Galán et al also examined the clinical efficacy of the NSCLC patients receiving pembrolizumab as firstline treatment according to the level of the ECOG PS using a single-center retrospective study [31]. In their study, the ORR, median PFS, and median OS in the patients with an ECOG PS 0-1 and an ECOG PS ≥ 2 were 26.1 and 5.7% (p = 0.014), respectively; 9.6 and 1.6 months (p < 0.001), respectively; and 18.9 and 2.0 months (p < 0.001), respectively [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Santini et al described that a higher proportion of NSCLC patients who had received ICIs within 30 days of death had a PS ≥ 2 [30]. Jiménez Galán et al also examined the clinical efficacy of the NSCLC patients receiving pembrolizumab as firstline treatment according to the level of the ECOG PS using a single-center retrospective study [31]. In their study, the ORR, median PFS, and median OS in the patients with an ECOG PS 0-1 and an ECOG PS ≥ 2 were 26.1 and 5.7% (p = 0.014), respectively; 9.6 and 1.6 months (p < 0.001), respectively; and 18.9 and 2.0 months (p < 0.001), respectively [31].…”
Section: Discussionmentioning
confidence: 99%
“…Jiménez Galán et al also examined the clinical efficacy of the NSCLC patients receiving pembrolizumab as firstline treatment according to the level of the ECOG PS using a single-center retrospective study [31]. In their study, the ORR, median PFS, and median OS in the patients with an ECOG PS 0-1 and an ECOG PS ≥ 2 were 26.1 and 5.7% (p = 0.014), respectively; 9.6 and 1.6 months (p < 0.001), respectively; and 18.9 and 2.0 months (p < 0.001), respectively [31]. They concluded that the ECOG PS was a single independent predictor of the OS and PFS found in their study.…”
Section: Discussionmentioning
confidence: 99%
“…ECOG PS has been identified as a prognostic factor of survival in patients with NSCLC treated with pembrolizumab in a first-line setting [33,34]. In a previously published study [15], we found that patients treated with pembrolizumab with ECOG PS ≥ 2 had a significantly shorter OS and PFS than those with ECOG PS of 0-1, with a median OS of 2 months and 18.9 months, respectively. However, the use of the ECOG as a prognostic marker is insufficient, and it is necessary to investigate other aspects related to the patient.…”
Section: Discussionmentioning
confidence: 60%
“…These findings have been shown in real-world data studies because clinical trials have excluded patients with PS ≥ 2 [13,14]. We recently published a study with real-life data in which patients with non-small lung cancer (NSCLC) and PS of 0-1 treated with pembrolizumab in a first-line setting had better clinical outcomes than patients with ECOG PS ≥ 2 [15]. This scale is the one most commonly used in cancer patients to assess their disability level.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation